2018
DOI: 10.1016/j.jand.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Nitrate Intake with the 15-Year Incidence of Age-Related Macular Degeneration

Abstract: Is there an independent association between dietary nitrate intake (from vegetable and non-vegetable sources) and the 15-year incidence of age-related macular degeneration (AMD)? Key Findings: In this prospective cohort study of 2037 participants (aged 49+ years at baseline), total nitrate intake and vegetable nitrate intake was significantly associated with incident early AMD, but not late AMD. Dietary intake of non-vegetable nitrate was not significantly associated with the 15-year incidence of early and lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
2
15
1
Order By: Relevance
“…Overall, the data obtained from this study show that the anti-oxidant and anti-apoptotic effects of flavonoids may limit neurodegeneration by providing neurotrophic support to prevent retinal damage in an animal model of autosomal dominant RP (Tvrm4 mice) as in other types of retinal diseases, such as diabetic retinopathy ( Al-Dosari et al, 2017 ) and AMD ( Maccarone et al, 2008 ; Falsini et al, 2010 ; Gopinath et al, 2018 ). In this work, we first used the Tvrm4 mouse model of RP to test the potential beneficial effects of two nutraceutical compounds, naringenin, and quercetin in single or combined administration, found in a typical Western diet, using a sub-chronic non-invasive treatment.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Overall, the data obtained from this study show that the anti-oxidant and anti-apoptotic effects of flavonoids may limit neurodegeneration by providing neurotrophic support to prevent retinal damage in an animal model of autosomal dominant RP (Tvrm4 mice) as in other types of retinal diseases, such as diabetic retinopathy ( Al-Dosari et al, 2017 ) and AMD ( Maccarone et al, 2008 ; Falsini et al, 2010 ; Gopinath et al, 2018 ). In this work, we first used the Tvrm4 mouse model of RP to test the potential beneficial effects of two nutraceutical compounds, naringenin, and quercetin in single or combined administration, found in a typical Western diet, using a sub-chronic non-invasive treatment.…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, these flavonoids show antioxidant properties that interact with the cellular detoxification enzyme system ( Al-Dosari et al, 2017 ). Furthermore, it has been shown that the anti-oxidant and anti-apoptotic effects of flavonoids can limit neurodegeneration by providing neurotrophic support to prevent retinal damage in RP as in other types of retinal disorders, such as diabetic retinopathy ( Al-Dosari et al, 2017 ) and age-related macular degeneration (AMD) ( Maccarone et al, 2008 ; Falsini et al, 2010 ; Gopinath et al, 2018 ). Our findings confirm, and extend, previous data published by other groups on the pivotal role of increased oxidative stress in photoreceptor death and the beneficial effects of antioxidant molecules in slowing retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these flavonoids exhibit anti-oxidant properties interacting with enzymatic system of cellular detoxification through a scavenger’s action (Al-Dosari et al, 2017). Furthermore, it has been demonstrated that the anti-oxidant and anti-apoptotic effects of flavonoids may limit neurodegeneration by providing neurotrophic support to prevent retinal damage in RP like in other kind of retinal disorders such as diabetic retinopathy (Al-Dosari et al, 2017) and Age-Related Macular Degeneration (Gopinath et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overfertilization of vegetables like lettuce, spinach, celery, and Chinese cabbage causes nitrate accumulation at levels of up to several g/kg fresh weight [44,45,46,47]. Possible health impacts of a high dietary intake of nitrate are intensively and controversially discussed [48,49,50,51,52,53,54,55].…”
Section: Introductionmentioning
confidence: 99%